Treatment outcome in new smear positive pulmonary tuberculosis patients with and without immunosuppression on RNTCP regimen: a comparative observational study - Muttath, Radhika; Andrews, Mekkattukkunnel; Prabhu, Dinesa (International Journal of Research in Medical Sciences, 2017)
Background: Immune status of a patient influences the susceptibility, clinical presentation of tuberculosis and its treatment outcome. Some of the most common conditions associated with immune deficiency includes, human immunodeficiency virus (HIV) infection, diabetes and chronic steroid therapy for any underlying diseases. Methods: A cohort study, enrolled patients with tuberculosis alone (n=51) and those with tuberculosis and immunosuppressed state (patients with HIV, diabetes and those on steroid therapy, n=97). Results: All patients received Directly Observed Treatment Short course (DOTS) regimen implemented through RNTCP. Among the immunosuppressed patients, 32 were HIV patients, 45 of them were diabetic and 20 received chronic steroid therapy. All immunocompetent patients (control) were totally cured but 62.5% and 88.9% of HIV and diabetic patients in the immunosuppressed group were cured. Mortality was high in the immunosuppressed group (18.75% in HIV, and 11.11% in diabetic group). The grade of sputum smear had significant influence on the treatment outcome after adjusting for death and default (p>0.05). After intensive phase, the smear conversion rate were 86.27% in the control group,37.5% in the HIV patients, 22.22% in diabetics and 55% among chronic steroid use. The mortality and cure rate among those who received treatment for diabetes mellitus is comparable with that of immunocompetent group. Treatment prolongation was required for patients in the immunosuppressed group (62.5% in HIV group, 77.7% in diabetes group and 45% in chronic steroid users group). Conclusions: Immunosuppression was a risk factor for increased morbidity and mortality among new smear positive pulmonary tuberculosis patients. Prolonged DOTS regimen requires long-term close follow-up of patients who are immunocompromised.